PENGUATAN KAPASITAS PEMASARAN LAYANAN AIR BERSIH BERBASIS KEPERCAYAAN KUALITAS PRODUK PADA KSM BANYU BENING ECO FRESH DI TANGERANG SELATAN - Sapto Yuwono; Brigida Endah Nuraeni; Edi Sumarya; Yozika Arvio; Sulastri Sulastri (Jurnal Pengabdian Bukit Pengharapan, 2025)
This study aims to examine the marketing strategy of clean water services implemented by the Community Self-Help Group (KSM) Banyu Bening in Taman Kedaung Housing, South Tangerang, with a particular focus on building consumer trust in potable water quality. The research adopts a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and documentation. In practice, KSM Banyu Bening conducts regular water quality testing through a local public health laboratory as a form of quality assurance and as a communication tool to inform the community. The findings reveal that the effectiveness of the marketing strategy is driven by transparency in communicating test results, the intensity of direct interaction with customers, and the utilization of community-based media for continuous information dissemination. This approach has proven effective in enhancing consumer trust and strengthening customer loyalty toward the clean water service. The study offers practical insights for developing trust-based marketing strategies in community-managed clean water services.